Students’ Perceptions of Family Entrepreneurship – A Study on Family Business Academic Education - Kansikas, Juha; Laakkonen, Anne (Management international / Gestiòn Internacional / International Management)

(untitled) (HEC Montréal et Université Paris Dauphine, 2009)
AbstractThe aim of this qualitative research is to analyze university students’ attitudes toward family entrepreneurship. The theoretical framework of the study analyzes the interaction between family business, ownership, and entrepreneurship education. 211 students from the University of Jyväskylä participated in the study during the basic business study course “Introduction to Entrepreneurship and Business Operations” in September 2007. 143 of those wrote a one page essay, either in Finnish or English, on family entrepreneurship and family business ownership. The students were told to write about the phenomena in their own words. The results were analyzed with content analysis in order to understand how to improve the development of family business entrepreneurship education. The results of the study show that family businesses are perceived through the concept of family: a family owns, works in, and manages a family business. Students perceive family businesses as small businesses that employ people locally. Entrepreneurship motivates students, but owning a family business was perceived as unattractive. The results of the study can be utilized in family business entrepreneurship education.